A Holistic Approach to Empower Micro Food Enterprises through Halal, Healthy, and Digital Practices - Illah Sailah; Khaswar Syamsu; Ahmad Faroby Falatehan; Mulyorini Rahayuningsih; Didah Nur Faridah; Sugiarto Sugiarto (Yayasan Keluarga Guru Mandiri, 2026)
Following the COVID-19 pandemic, the Pasar OnlinePakcycommunity in thePakuanRegency residential area expanded significantly; however, home-based online food production has largely operated without adequate oversight and limited knowledge of halal compliance, food safety, and hygienic processing. These conditions highlighted the need for holistic training and mentoring to improve product quality, halal literacy, and digital marketing professionalism among local micro food enterprises. This community empowerment program aimed to strengthen microenterprises through integrated training on halal ingredients, healthy food processing, appropriate packaging, and digital marketing. The program involved 40 participants and applied a holistic approach combining lectures, hands-on practice, and post-training mentoring. Knowledge gains were measured using pre- and post-tests, while short-term impacts were assessed through a follow-up survey conducted two months after training and observation of participants' activities in the community's WhatsApp group as a marketing platform. Results showed an increase in knowledge. Survey findings indicated high perceived usefulness, increased self-confidence, and improved understanding of halal principles. Observations revealed better promotional images, clearer pricing, and more effective communication. Overall, integrated training supported by digital community platforms enhanced knowledge and marketing practices, contributing to more competitive, halal, and sustainable micro food businesses.